Impact of population movement on the spread of 2019-nCoV in China. Issue 1 (1st January 2020) - Zhang, Chi; Chen, Cai; Shen, Wei; Tang, Feng; Lei, Hao; Xie, Yu; Cao, Zicheng; Tang, Kang; Bai, Junbo; Xiao, Lehan; Xu, Yutian; Song, Yanxin; et al.
ABSTRACT: Since Dec 2019, China has experienced an outbreak caused by a novel coronavirus, 2019-nCoV. A travel ban was implemented for Wuhan, Hubei on Jan 23 to slow down the outbreak. We found a significant positive correlation between population influx from Wuhan and confirmed cases in other cities across China (R 2  = 0.85, P  < 0.001), especially cities in Hubei (R 2  = 0.88, P  < 0.001). Removing the travel restriction would have increased 118% (91%–172%) of the overall cases for the coming week, and a travel ban taken three days or a week earlier would have reduced 47% (26%–58%) and 83% (78%–89%) of the early cases. We would expect a 61% (48%–92%) increase of overall cumulative cases without any restrictions on returning residents, and 11% (8%–16%) increase if the travel ban stays in place for Hubei. Cities from Yangtze River Delta, Pearl River Delta, and Capital Economic Circle regions are at higher risk.